Nanny Fox and the Christmas surprise - Adams, Georgie (Doubleday Book for Young Readers, 1996)
Arnold Fox proves his worth as a nanny when he manages to save the chicks in his care from other foxes who have disguised themselves as Santa Claus and his reindeer.